Evaluation of confirmatory data following the Article 12 MRL review for tebufenpyrad. (16th February 2023) - ,; Bellisai, Giulia; Bernasconi, Giovanni; Brancato, Alba; Carrasco Cabrera, Luis; Castellan, Irene; Del Aguila, Monica; Ferreira, Lucien; Santonja, German Giner; Greco, Luna; Jarrah, Samira; Leuschner, Renata; et al.
Abstract: The applicant Belchim Crop Protection submitted a request to the competent national authority in Germany to evaluate the confirmatory data that were identified for tebufenpyrad in the framework of the maximum residue level (MRL) review under Article 12 of Regulation (EC) No 396/2005 as not available. To address the data gaps, new residue trials on peaches, apricots and raspberries (extrapolated to blackberries and dewberries) as well as a new analytical method for enforcement in animal commodities and its independent laboratory validation were submitted. The data gaps were considered satisfactorily addressed. The new information provided required a revision of the existing MRLs for peaches and apricots while the existing MRLs for blackberries and dewberries could be confirmed. An update of the consumer risk assessment for tebufenpyrad was performed in light of the new data submitted and it did not indicate any consumer intake concerns in relation to the chronic exposure and the acute exposure of the crops under consideration in the present assessment.